2001
DOI: 10.1509/jppm.20.1.93.17291
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Individualism, Collectivism, and Locus of Control on Environmental Beliefs and Behavior

Abstract: This study investigates the influence of value orientations measured at the individual level (individualism, collectivism, and locus of control) and of economic status on environmental beliefs and behavior. Structural equation modeling reveals that the preferred model is one in which the value orientations and economic status influence beliefs about recycling, which in turn influence recycling behavior, but the influence of the value orientations and economic status differs as a function of the type of enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
393
1
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(422 citation statements)
references
References 38 publications
(50 reference statements)
17
393
1
11
Order By: Relevance
“…Thus, a person who thinks collectively is expected to protect the environment so that the whole society, including himself/herself, can enjoy prosperity (McCarty & Shrum, 1994). The positive association between collectivism and environmentally-friendly attitudes (both inward and outward) was repeatedly confirmed in previous empirical studies (e.g., Ling-yee, 1997;Chan, 2001;McCarty & Shrum, 2001). Based on the above argumentation, we may predict that:…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Thus, a person who thinks collectively is expected to protect the environment so that the whole society, including himself/herself, can enjoy prosperity (McCarty & Shrum, 1994). The positive association between collectivism and environmentally-friendly attitudes (both inward and outward) was repeatedly confirmed in previous empirical studies (e.g., Ling-yee, 1997;Chan, 2001;McCarty & Shrum, 2001). Based on the above argumentation, we may predict that:…”
supporting
confidence: 55%
“…Some of the measures employed were: personal values, such as security, fun/enjoyment, and self-gratification (e.g., McCarty & Shrum, 1994;Jansson, Marell, & Nordlund, 2010); ethical ideologies, such as deontologism and teleologism (e.g., Spash, 1997;Chan et al, 2008); societal factors, such as liberalism and social altruism (e.g., Straughan & Roberts, 1999;Paladino, 2005); cultural orientations, such as collectivism and individualism (e.g., Laroche, Bergeron, & Barbaro-Forleo, 1999;McCarty & Shrum, 2001); and personal environmental beliefs, such as faith in others, perceived consumer effectiveness, and susceptibility to normative influence (e.g., Ellen et al,. 1991;Minton & Rose, 1997;Smith & Paladino, 2010).…”
Section: Previous Researchmentioning
confidence: 99%
“…In a similar vein, McCarthy and Shrum (2001) found that collectivism positively impacted on consumers' recycling and their recycling behaviour. According to these researchers, consumers with individualistic tendencies viewed recycling as less important but those who are collectivistic, have a higher tendency to cooperate, are willing to help others and stressed achieving group goals rather than personal goals (McCarthy & Shrum, 2001). …”
Section: Value Orientationmentioning
confidence: 99%
“…With relevance to behaviour though, the relevant scores are never high. As stated by McCarty and Shrum (2001), 'when a consumer acts pro-environmentally the cost for the individual is immediate, while the benefit is at best long-term or even not visible'.…”
Section: T Here Have Been Many Suggestions During the Last Three Decamentioning
confidence: 99%